Environmental distribution patterns and sustainability assessment of mitre squid Uroteuthis chinensis in the waters of Bangka, Indonesia - VALENTIN VINA RATNAPURI; MONISCHA BR SEBAYANG; MUHAMAD FATHUR ROZAKI (Society for Indonesian Biodiversity, 2026)
Abstract. Ratnapuri VV, Sebayang MB, Rozaki MF. 2026. Environmental distribution patterns and sustainability assessment of mitre squid Uroteuthis chinensis in the waters of Bangka, Indonesia. Biodiversitas 27 (5): d270517. https://doi.org/10.13057/biodiv/d270517. The waters of Bangka were among the main mitre squid Uroteuthis chinensis production areas in Indonesia, but they showed signs of increased exploitation pressure that could affect stock sustainability. This study aimed to integrate the satellite-based Environmental Suitability Index and Maximum Sustainable Yield for mitre squid in Bangka, with a monthly distribution resolution that explicitly distinguished between productive and non-productive seasons. Satellite imagery data and catch landings were used for the period September 2024-August 2025, while the Maximum Sustainable Yield was estimated for the period 2020-2024. The weighting of environmental parameters in the Environmental Suitability Index (ESI) was conducted through Principal Component Analysis and Pearson Correlation. The results showed that the Environmental Suitability Index value had a strong and significant positive relationship with CPUE (r: 0.838; p: 0.001; R²: 0.6503), with periods of moderate to high ESI values (≥0.4) being associated with increased CPUE (0.539-0.755 ton/trip), while low ESI values (<0.4) were associated with low CPUE (0.017-0.552 ton/trip). On the other hand, sea surface temperature (29.558-30.848°C) and chlorophyll-a (0.279-0.375 mg m-³) did not show a significant linear relationship with CPUE, thus were interpreted as indicators of habitat conditions rather than direct drivers of productivity. The Maximum Sustainable Yield analysis showed that in 2023, production reached 9,157 tons, exceeding the Maximum Sustainable Yield estimate of 7,865 tons (16.43%), with an effort level of 65,513 trips, surpassing the Fopt of 35,800 trips (82.72%), thereby indicating potential fishing pressure. Overall, these findings affirmed that the multivariate approach based on the Environmental Suitability Index was more effective in representing habitat suitability and highlighted the importance of seasonally adaptive management. However, the interpretation of results and management recommendations in this study required further validation through long-term data and scenario-based implementation before operational application.